Global warming expectations of German firm representatives are overly optimistic, uncertain, and easily influenced - Dominik Schober; Claudia Schmiedeberg (npj Climate Action)
Abstract What expectations do firm representatives hold regarding future climate change, and how certain are they in their expectations? We analyze German firm representatives’ expectations and effects of the firms’ policy affectedness and engagement, and firm representatives’ knowledge using an information treatment experiment. We find modest economic sector differences and a positive association of engagement (i.e., energy and emission metering and reduction target setting) with expected global warming. The information treatment increases the global warming expectations in the optimistic (low warming) scenarios and decreases expectations in the pessimistic (high warming) scenarios. Moreover, representatives from less engaged firms appear rather uncertain and overly optimistic and tend to be pushed upwards in their expectations by the information treatment, while a downward shift is observed among the more engaged firms. Our results imply that the majority of respondents have a high degree of uncertainty and limited knowledge regarding climate change and appear easily influenceable.